Works in the Cathedral of Lugo during the second half of the 18th century: the Influence of Antonio Cosentino de Tejada - Calles Lombao, Marcos Gerardo (Huarte de San Juan. Geografía e Historia, 2022)
The emptying of the Archive of the Cathedral of Lugo and the Provincial Historical Archive of Lugo, of the documentation linked to the works in the Basilica of Santa María of Lugo during the 2nd half of the 18th century, shows the influence of the canon and archdeacon of Neira Antonio Cosentino de Tejada. His positions as butler of the prelate Francisco Izquierdo Tavira, as a fabricator or as secretary of the Council of Canons, have made it possible to have numerous documents in which he appears, linked to the reforms of the temple. The new Main Chapel, the relocation of the Cornielles de Holanda altarpiece or the construction of the Good Jesus façade, are some of the examples in which the figure of Antonio Cosentino de Tejada appears promoting, or managing, the future of some works that are among the most outstanding of this basilica from Lugo, a building included in the World Heritage by UNESCO in 2015.